Prevalence and Risk Factors of Postprocedure Depression in Patients with Atrial Fibrillation after Radiofrequency Ablation - Mingli Du; Tieniu Cheng; Yutong Ye; Yong Wei (Cardiology Research and Practice)
Background. Recent studies have shown a bidirectional relationship between atrial fibrillation (AF) and psychological depression. However, little is known about the prevalence of postprocedure depression (PPD) in patients with AF at the time of radiofrequency (RF) ablation. Objective. To describe the prevalence and identify risk factors for PPD. Methods. This was a prospective cohort study, including 428 AF patients who were willing to undergo the first catheter ablation in our hospital from 1st April to 30th December 2019. The primary outcome was PPD, which was determined by Hospital Anxiety and Depression Scale-Depression. Results. The prevalence of PPD was 16.8% (72/428) in our cohort, without difference between men (16.0%, 41/256) and women (18.0%, 31/172) (P = 0.586) but with a great difference among different age groups (P = 0.016). On the univariable binary logistic regression analysis, age, a history of coronary heart disease, Observer’s Assessment of Alertness/Sedation (OAA/S) score when ablating at the specific position, and OAA/S score when pulling out the catheter sheath were associated with PPD. Subsequent multivariable logistic regression analysis indicated only age (OR 0.96, 95% CI: 0.94–0.99, P< 0.01) and OAA/S score when ablating at the specific position (OR 0.58, 95% CI: 0.39–0.88, P = 0.01) were independently associated with PPD. Conclusion. PPD is common in patients with AF after RF ablation. Younger age and lower OAA/S score when ablating at the specific position are its most significant risk factors. Intensive management of sedation may be of great importance for reducing PPD. This trial is registered with the Chinese Clinical Trial Registry (ChiCTR2200057810).